Late Pleistocene-Holocene fluvial records of the Wadi Dishshah: hydro-climatic and archaeological implications (Southern piedmont of the Hajar Mountains, Oman) - Desruelles, Stéphane (2022)
In Oman, quaternary climatic fluctuations alternated between humid and arid periods. Humid periods are a key component in landscape evolution and the history of early human-environment interactions, as they allowed for less-restrictive arid conditions by triggering increasing rainfall and fluvio-lacustrine activity. Fluvial archives are of great interest for understanding hydrosystems’ local responses to quaternary regional climatic fluctuations. For the end of the Pleistocene and the Holocene, little data are available in Northern Oman to examine this topic and to compare it with archaeological site distribution and subsistence strategies, in particular with regard to water resources. Here, we will present fluvial records from a small wadi called Wadi Dishshah, located in the southern part of the Hajar Mountains’ piedmont, near the Salakh Arch area. The study of the Wadi Dishshah relies on topographic surveys (aerial survey with drone), geomorphological mapping, morphostratigraphic analyses of natural and excavated sections, malacological analyses and age-dating using OSL and radiocarbon methods. Three phases of aggradation have been identified: the first one between 26,500 cal. BP and 11,300 cal. BP, a second between 6,200 cal. BP and 5,500 cal. BP and a late one around 2,800 cal. BP. The fluvial records from the Wadi Dishshah and its hydro-climatic significance are compared to the distribution of archaeological sites from the Salakh Arch area to discuss the relations between settlement strategies and surface flows. This work is the first case study of late Pleistocene – Holocene alluvial formations in this region of Oman.